The influence of variative learning models on the critical thinking skills of multiethnic state junior high school students in Ternate City - Ermin; Arifin , As’ad Syamsul (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Critical thinking is an essential skill that enables students to analyze, evaluate, and solve problems rationally and reflectively. However, learning practices show that students’ critical thinking skills remain relatively low, indicating the need for more effective instructional strategies. This study aimed to examine the effects of the STAD model, the NHT model, and a combination of STAD and NHT on the critical thinking skills of multiethnic junior high school students in Ternate City. This study employed a quasi-experimental method using a pretest–posttest nonequivalent control group design. The population consisted of all Grade VII multiethnic students in Ternate City junior high schools, with a sample of 76 students comprising 20 Ternate, 27 Makian, and 29 Tidore students. Research instruments included observation sheets and critical thinking skill tests. Data were collected through pretests and posttests and analyzed using descriptive statistics and inferential statistics with analysis of covariance (ANCOVA) at a 0.5% significance level.The results showed that learning models significantly affected students’ critical thinking skills. The STAD model combined with NHT resulted in higher critical thinking skills than STAD, NHT, and conventional learning. Ethnicity also had a significant effect, with Ternate students demonstrating higher critical thinking skills than Makian and Tidore students. Furthermore, the interaction between learning strategies and ethnicity significantly influenced students’ critical thinking skills. Overall, the combination of STAD and NHT was found to be effective in improving the critical thinking skills of students from all ethnic groups.